Globalizing India - Assayag, Jackie (ed); Fuller, C J (ed) (London, 2005)
This is one of the earliest books to present a collection of writings on the effects of globalization on India and Indian society. The very concept of globalization needs critical examination, and one productive approach is to focus specifically on the local impacts of globalization in its various guises through comparative ethnographic investigations. Such research also permits examination of the relative significance of globalization, as opposed to national, regional or local factors of change that may actually be more salient. Assayag and Fuller have assembled a team of eminent academics, who present a series of critical discussions about important issues of economy and agriculture, education and language, and culture and religion, based on ethnographic case studies from different localities in India. This challenging collection also includes a major study of the history of globalization and India that sets current trends in perspective.
Keywords: Globalization